Effects of Upper Eyelid Blepharoplasty on Contrast Sensitivity in Dermatochalasis Patients - Hilal Nalcı; Melek Banu Hoşal; Ömür Uçakhan Gündüz (Türk Oftalmoloji Dergisi, 2020)

(untitled)
Objectives:To evaluate the impact of upper eyelid blepharoplasty on contrast sensitivity in dermatochalasis patients.Materials and Methods:Best corrected visual acuity, ophthalmologic examination, eyelid examination, lash ptosis, contrast sensitivity using sine-wave contrast sensitivity chart, keratometric parameters, and corneal aberrations of 34 eyes of 34 patients who underwent upper eyelid blepharoplasty due to dermatochalasis in our clinic between the years 2014 and 2018 were evaluated preoperatively and at postoperative 3 months.Results:Twenty-three (68%) of the patients were females and 11 (32%) were males. Mean age was 63.1±7 (52-81) years. Mean best corrected visual acuity was 0.036±0.06 (0-0.15) logMAR preoperatively and postoperatively (p>0.05). Contrast sensitivity values of the patients at the frequencies of 1.5, 3, 6, 12, and 18 cycles per degree were 44.38±19.5, 59.03±27.2, 41.44±34.1, 15.15±19.3, and 5.15±4.26 preoperatively and 44.80±20.9, 76.85±33.4, 63.21±46.4, 28.21±31.1, and 10.5±9.5 postoperatively, respectively. The difference between contrast sensitivity values was statistically significant at the frequencies of 3, 6, 12, and 18 cpd (p=0.005, =0.001, <0.001, and <0.001, respectively). Although lash ptosis of the patients improved significantly after the surgery, there was no correlation between lash ptosis improvement and change in contrast sensitivity (p>0.05). Keratometric values and corneal high order aberrations did not change significantly after the surgery (p>0.05).Conclusion:Contrast sensitivity significantly increases after upper eyelid blepharoplasty, especially at higher spatial frequencies which are known to deteriorate due to age-related changes in the lens and retina in older adults. Our results show that blepharoplasty may have additional functional indications for elderly dermatochalasis patients in terms of improving the functions such as performing daily tasks and reading.